2-aryloxybenzo[d]oxazoles as deep blue solid-state emitters: Synthesis, aggregation-induced emission properties and crystal structure. (March 2021) - Meng, Yuanyuan; Fang, Ying; Yuan, Chunming; Du, Chunhui; Wang, Kun-Peng; Chen, Shaojin; Hu, Zhi-Qiang
Abstract: The design and exploration of efficient organic fluorophores have attracted significant scientific interest for their various potential applications. As blue fluorescent materials are essential for the achievement of a full-color display and white emission, the development of new efficient organic blue-emitting materials is of great importance. In this work, we found that simple organic molecules 2-aryloxybenzo[d]oxazoles could act as novel organic fluorophores with special AIE properties and efficient blue fluorescent emission in the solid states. Compounds 3 and 4 possess moderately high quantum yields at 10.3% and 11.4%, respectively. The CIE coordinates indicate that most of these compounds are deep-blue emitters. The single crystal structure of compound 3 shows that it has a twisted V-shape molecular structure with J-type aggregation. Noncovalent interactions widely exist in the crystal structures, while π-π stacking interactions are not observed between adjacent aromatic rings. The special fluorescent properties of these new emitters could ascribe to the unique molecular packing mode in the crystal structure. This work provides a new strategy to access organic solid-state fluorophores with deep-blue emission. Graphical abstract: Simple organic molecules (2-aryloxybenzo[d]oxazoles) act as novel organic fluorophores with special AIE properties and efficient deep blue fluorescent emission in the solid states. Image 1 Highlights: 2-Aryloxybenzo[d]oxazoles derivatives are designed and synthesized. These fluorophores show special AIE properties. These compounds exhibit efficient deep blue emission in solid states.